Effect of protein supplementation on dormant, bluestem-range forage intake and digestion and protein flow to the small intestine in steers - Hannah, S.M.; Cochran, R.C.; Harmon, D.L.; Vanzant, E.S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A digestion trial was conducted to determine dormant, bluestem-range forage intake, digestion, and protein flow to the small intestine in steers receiving different crude protein (CP) supplements. Dietary treatments were 1) control: no supplement; 2) low protein supplement (Low-CP): SBM + grain sorghum supplement containing 13% CP; 3) moderate protein supplement (Mod-CP): SBM + grain sorghum supplement containing 26% CP; and 4) dehydrated alfalfa pellets supplement (Dehy): supplement containing 17.5% CP. Forage intake increased an average of 36% in steers supplemented with Mod-CP and Dehy, compared to the forage intake of control steers. Forage intake of steers receiving Low-CP supplement was similar to that of control steers. Total tract digestion of forage fiber increased 8% when Mod-CP and Dehy supplements were fed compared to control treatment, whereas Low-CP supplement caused an 11% decrease in fiber digestion compared to control treatment. Crude protein flowing into the small intestine was greatest for steers fed the Mod-CP and Dehy supplements. In conclusion, the Dehy supplement was as effective as the Mod-CP supplement when fed to provide the same amount of CP per day; however, when a grain-based supplement was fed, increasing the CP concentration above 20% significantly improved intake and utilization of poor-quality range forage.
Keywords: Beef; Protein supplements; Intake; Crude protein flow; Winter range